Cover Image. (18th April 2020) - Gold, Michael H.; Kinney, Brian M.; Kaminer, Michael S.; Rohrich, Rod J.; D'Amico, Richard A.
Abstract : The cover image is based on the Original Contribution A multi‐center, open‐label, pilot study of allograft adipose matrix for the correction of atrophic temples by Michael H. Gold et al., https://doi.org/10.1111/jocd.13363 .